A study on the media ownership regulations in the Communications and Multimedia Act 1998 / Hamizah Mohd Senon, Siti Izzora Rush and Syed Muhammad Adeeb Barakbah - Mohd Senon, Hamizah; Rush, Siti Izzora; Barakbah, Syed Muhammad Adeeb (2011)
This study is on "Media Ownership Regulations in the Communications & Multimedia Act (CMA) 1998, is completed as a fulfillment of the course of Bachelor of Legal Studies (Hons.). The study concerns mainly on the ownership of the numerous media stations in Malaysia and its impact on democracy and economy. The research is done on the basis of the national objectives under the CMA 1998 which calls for establishing Malaysia as a major global centre and hub for communications and multimedia information and content services. This research addressed the issue of the current media ownership in Malaysia being highly concentrated in the hands of a few and it is linked to political parties. This may endanger the democracy of the people as information may be influence by certain political views. The objective of this research is to find out whether such structural media ownership regulations that exist in the United States and Australia is suitable to be adapted in Malaysia through the CMA 1998 in order to prevent concentration of media ownership. Thus, this research analysed the structural regulations of media ownership in the US and Australia. This research discovers that the structural media ownership regulations are not suitable to be adapted into the Malaysian media industry due to factors such as the size of the market and lack of media players. Thus, recommendations are given to improve the situation of the current media in Malaysia as an alternative to the structural media ownership regulations.